ANALISIS DIVIDEND PAYOUT RATIO DAN DEBT TO EQUITY RATIO TERHADAP KINERJA KEUANGAN PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2021 – 2023 - Titi Aslah; Endar Julianah; Anisa Nabila (Journal of Information System, Applied, Management, Accounting and Research, 2026)
This study analyzes the effect of the Dividend Payout Ratio (DPR) and Debt to Equity Ratio (DER) on the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The population consists of 13 companies, with a sample of 11 companies meeting the criteria. This research employs a quantitative approach with a documentation technique, collecting secondary data from annual financial reports published on www.idx.co.id. Data analysis was conducted using classical assumption tests, multiple linear regression, correlation analysis, t-test, and F-test with the assistance of SPSS version 20. The results indicate that DPR does not significantly affect Return on Equity (ROE), with a t-value of -1.083 < t-table 2.04227 and a significance level of 0.287 > 0.050. An increase in DPR tends to decrease ROE, as dividends reduce reinvested earnings. Meanwhile, DER has a negative effect on ROE, with a t-value of -18.039 > t-table 2.04227 and a significance level of 0.000 < 0.050. High reliance on debt can lower profitability and increase financial risk. Simultaneously, DPR and DER significantly affect ROE, with an F-value of 168.456 > F-table 3.32 and a significance level of 0.000 < 0.05. DPR reflects profit distribution policies, while DER influences capital structure, providing insights into corporate financial management strategies to maximize profitability.